Anaxagorea luzonensis A. Gray: A New Annonaceae Plant Collection of Purwodadi Botanic Garden - Lestari, Dewi Ayu (Proceeding International Conference on Global Resource Conservation, 2013)
Annonaceae collection in Purwodadi Botanic Garden consist of 49 genera, 51 species, 381 specimens, 117 collection numbers are unknown species and 23 collection numbers are undetermined. One of them is an Annonaceae collection in XVIII.E.26. Since planting on December 21st, 1996 until now the collection is undetermined plant species. The purpose of this study was to determine species of the collection based on morphological characters. The result shows that its plant collection belonging to the genera of Anaxagorea. Description based on morphological characters indicates that the Annonaceae collection is Anaxagorea luzonensis and a new Annonaceae plant collection in Purwodadi Botanic Garden. Description of Anaxagorea luzonensis is shrubs, stem cylindrical, brown colored, leaves single, alternate. Petiole short, leaf texture is herbaceous, leaf surface glabrous, leaf blade ellipse, and oval until lanceolate; base obtuse to acute, apex acute, apiculate to obtuse; leaf edges entire, green colored in abaxial and adaxial leaf. Primer veins are pinnate. Secondary veins 9-11 on each side of midvein, rarely. Tertiary vein prominently and clearly in abaxial leaf. Flower opposite with leaves, solitary, ca. 0,6 x 1 cm, pedicel ca. 0,5 cm. Sepal 3, rounded to ovate, 0,25 x 0,3 cm, greenish, smooth. Petals 6, in two whorls, 3 outer petal ovate, 1,1 x 0,7 cm, smooth, white, slightly longer and 2x broader than inner petals. 3 inner petal ovate, 1 x 0,4 cm, smooth and white. Stamen many and yellowish colored. Pistil 4 and whitish colored. Carpel 2-4, fruit greenish colored. Â Keywords: Anaxagorea, Annonaceae, morphology character, Purwodadi Botanic Garden